Redes sociales, tejidos de paz (2019)
New languages, from immersion technology to which today's society has voluntarily submitted, need to be analyzed from the perspectives generated by new ways of relating. So it is not unusual to find several networks simultaneously connected in a common space; the criteria taken into account to include or invite partners to these common spaces, and that should respond to the tastes and interests of all, do not always result as it ought to be. The work of building relationships through online communication tools makes it possible to create networks, not only to build relationships, but to generate new knowledge through them. Networking experiences that identify efforts to create a peaceful society require specific attention and care so the construction achieved leaves out the vices that threaten the durability that everyone desires in their interpersonal relationships.